38
4. Laplace Transform
We will not prove the theorem. However, the examples below will show why it isreasonable.
Example 4.6.
Compute
L
(1).
Solution
. Let’s apply Theorem 4.5 to see what to expect. The function
f
(
t
) = 1 isexponentially bounded. Indeed, we can choose
k
= 1,
a
=
M
= 0 in (4
.
2). Theorem4.5 then implies the Laplace transform exists for all
s > a
= 0.To ﬁnd the
L
(1) we compute it using the deﬁnition
L
(1) =
∞
0
e
−
st
1
dt
= lim
A
→∞
−
1
se
−
st
A
0
= lim
A
→∞
1
s
(1
−
e
−
As
)
.
The limit of the exponential is zero as long as
s >
0. Therefore,
L
(1) =1
s, s >
0as expected.
Example 4.7.
Compute
L
(
e
at
).
Solution
. Again we apply Theorem 4.5 to see what to expect. The function
f
(
t
) =
e
at
is exponentially bounded if we choose
k
= 1,
a
=
a
,
M
= 1 in (4
.
2).Theorem 4.5 then implies the Laplace transform exists for all
s > a
.To ﬁnd the
L
(
e
at
) we compute it using the deﬁnition
L
(
e
at
) =
∞
0
e
−
st
e
at
dt
=
∞
0
e
(
a
−
s
)
t
dt
= lim
A
→∞
−
1
a
−
se
(
a
−
s
)
t
A
0
= lim
A
→∞
1
s
−
a
(1
−
e
A
(
a
−
s
)
)
.
We need the exponent to be negative for the limit to exist. This is the case provided
s > a
. Therefore,
L
(
e
at
) =1
s
−
as > a.
The next example is more diﬃcult, but it shows the usefulness of the Laplacetransform.
Example 4.8.
Compute
L
(
f
′
(
t
)), where
f
is a piecewise smooth exponentiallybounded function.
Solution
. We are told there exists
k
,
a
, and
M
such that

f
(
t
)
 ≤
ke
at
for all
t
≥
M
. We use the deﬁnition of Laplace transform and integrate by parts
L
(
f
′
(
t
)) =
∞
0
e
−
st
f
′
(
t
)
dt
= lim
A
→∞
A
0
e
−
st
f
′
(
t
)
dt
= lim
A
→∞
e
−
st
f
(
t
)
A
0
+
A
0
se
−
st
f
(
t
)
dt
= lim
A
→∞
e
−
sA
f
(
A
)
−
f
(0) +
A
0
se
−
st
f
(
t
)
dt
.